The intimate and the impossible: analogy without similitude in Jean-Luc Marion - Knight, T (2016)
In this thesis I argue that the constructive philosophical project of Jean-Luc Marion offers a new way of thinking the analogical relation between God and the human person. I particularly examine his concept of the saturated phenomenon in order to show how we might construct the relation between incommensurable terms (God and the human being) without requiring a similitude to mediate the relation. I argue that for Marion God's transcendence is understood as what he describes as "impossibility" and that his immanence is understood through Augustine's interior intimo meo, the God more intimate to me than I am too myself. I demonstrate that radical immanence is God's transcendence insofar as the event of the impossible precedes the being-possibility correlation of metaphysics. Thus I develop the relation of God and the human being as a coincidence of opposites more than an analogy: the infinite distance of radical alterity becomes a belonging together of the human being with God. As a consequence of this analysis, I develop a new concept of relation, which I call "hyperbolic relation." If similitude always threatens to abolish the alterity of the terms of the relation (as was Barth's objection to the analogia entis), in this case, alterity is maintained not by removing relation but by increasing it to the level of hyperbole. Like Marion’s God who is "without Being," this analogy is "without similitude" by means of excess. The concept of God that I develop (impossible as intimate and vice versa) will consequently lead to a deepening of the concept of the human person through the transfiguration that saturation precipitates within the concept of relation.